Thermal behavior of the Ti(IV), Zr(IV) and Pb(II) complexes with 5-nitro-8-hydroxyquinoline - Crespi, Marisa Spirandeli [UNESP]; Zorel, H. E.; Ribeiro, Clovis Augusto [UNESP] (Kluwer Academic Publ, 2003)
Ti(IV), Zr(IV) and Pb(II) complexes with 5-nitro-8-hydroxyquinoline (5-NQ) were obtained by precipitation in acetone/ammonium solution medium. The compounds TiO(C9H5N2O3)(2).0.5H(2)O, ZrO(C9H5N2O3)(2)2H(2)O and Pb(C9H5N2O3)(2) were characterized by Elemental Analysis, X-ray Diffratometry and Infrared Absorption Spectrometry and their thermal behavior followed by TG/DTA. This present study intends to show the variations in the thermal behavior of the compounds and in the composition and/or structure of final oxide residues, in different atmospheres and heating rates.
Keywords: complexes; 5-nitro-8-hydroxyquinoline; TG/DTA; thermal behavior